Interaction eﬀect of boron and zinc on growth, yield and quality of chilli (Capsicum annuum) - Krishan Kant Tyagi; Rajendra P Maurya; Radha Kushum; Regar , Kavita; Sandeep Verma (Current Horticulture, 2025)
The study was carried out at School of Agriculture, Suresh Gyan Vihar University, Jaipur (Rajasthan), during 2022-23, in Factorial Randomized Block Design, comprising nine treatment combinations, viz. control (T0), boron @ 0.2% (T1), boron @ 0.4% (T2), zinc @ 0.2% (T3), zinc @ 0.4% (T4), boron @ 0.2% + zinc @ 0.2% (T5), boron @ 0.2% + zinc @ 0.4% (T6), boron @ 0.4% + zinc @ 0.2% (T7) and boron @ 0.4% + zinc @ 0.4% (T8). The treatments were replicated three times. The eﬀect of diﬀerent concentrations of micronutrients on growth, yield and quality attributes were signiﬁcantly inﬂuenced by diﬀerent concentrations of boron and zinc under local agroclimatic conditions of Jaipur. The maximum (31.64 cm) and (49.98 cm) plant height at 45 and 60 DAT, respectively, 162.47 leaves per plant, 14.54 branches per plant, 16.67 ﬂower clusters per plant, 50.10 fruits per plant, (2.66 cm) fruit girth, minimum (45.10 days) and (50.03 days) took for 50% ﬂowering and ﬁrst harvesting, respectively and longest (8.15 cm) fruit length, heaviest (11.79 g) fruit and maximum (468.73 g/plant and 18.03 t/ha) green chilli yield and (3.20 t/ha) dry red chilli yield and highest B: C ratio (3.25)were recorded under foliar spray of boron @ 0.2% + zinc @ 0.4% treatment. Hence, foliar application of boron @ 0.2% + zinc @ 0.4% performed signiﬁcantly superior over control and remaining treatments to get highest green chilli production.